Keanekaragaman Jenis Burung di Banda Aceh dan Aceh Besar - Aki Handayani Tambak; Cut Zsa Zsa Sufinta; Ikbal Maulana; Delia Marwah Rafiah; Muhammad Hanif; Aida Fithri; Widya Sari (Universitas Syiah Kuala, 2024)
Birds are wild animals that have high adaptability to a wide variety of habitat types. This review article aims to determine the diversity of birds found in several areas in Aceh Province. Data collection was carried out using library study techniques, namely tracing sources or literature in the form of primary data in the form of national journals, theses, dissertations, and proceedings for the last 16 years (2007 - 2023). The total bird species found in the above areas was 139. The diversity of birds in several areas in Aceh Province, such as in Lhoknga District, Aceh Besar Regency, Aceh Besar Mangrove Forest After the 2004 Tsunami, Deudap Pulo Aceh Aceh Besar Regency, Banda Aceh City Forest, Mount Seulawah Agam Aceh Besar, TAHURA Pocut Meurah Intan Aceh, in the green open spaces of Banda Aceh City, the East Coast of Banda Aceh City, the Glee Nipah area of ​​Pulo Aceh, Kilometer Zero Iboih Pulau Weh Sabang, as well as at Kawasan Ekosistem Leuser Wilayah Menggamat Desa Arie Buluh Kabupaten Aceh Selatan.